Clinical training groups for spirituality and religion in psychotherapy. Issue 3 (3rd July 2019) - Rupert, David; Moon, Sarah H.; Sandage, Steven J.
ABSTRACT: Clinical training in spirituality and religion (S/R) is an important dimension of cultural competence. We outline a relational approach to S/R issues in clinical practice, and then describe a key relational training component, SERT groups. SERT is an acronym that references the diverse, multifaceted spiritual and existential issues that may emerge in psychotherapy. SERT groups are small training groups that utilize intentional conversation, diversity, and relational dynamics to cultivate capacities for addressing S/R dynamics in clinical practice. We describe the structure and format of SERT groups, common topics, guidelines for facilitators, and possibilities for tailoring this approach in other contexts.